الأكسدة الأنزيمية المحفزة بإنزيم اللاكاز للكاتشين في وسط ثنائي الطور (عضوي/مائي) والفعاليات البيولوجية للمنتجات النهائية الموافقة - عيسى, نزار (Latakia University Journal -Biological Sciences Series, 2019)
In the present study, a green procedure for the synthesis of nature identical stable compounds by laccase-catalyzed oxidation of catechin in a hydro-organic biphasic system was investigated. Catechin was chosen because it is one of the effective flavonoids present in the human diet with various biological activities. Additionally, this work aimed to exploit the laccase-catalysed oxydation of catechin in a hydro-organic biphasic system in order to increase the solubility of the resulting products, effectiveness in the prevention of their subsequent browning and to improve their biological activities. Myceliophthora thermophila laccasecatalyzed oxidation of (+)-catechin, was carried out in aqueous and hydro-organic medium to synthesize new active molecules. The ultrafiltration of the commercial laccase allowed for the elimination of phenolic contaminants and increased the specific activity by a factor of 2. The oxidation of (+)-catechin in a biphasic hydro-organic system (perfectly mixed) consisting of ethyl acetate and sodium–phosphate buffer resulted in intermediate stable orange products. Compared to the aqueous medium, the biphasic hydro-organic medium presenented significant advantages such as decreased the activity of the laccase, an increased effectiveness in the prevention of browning and an increased solubility and stability of the resulting intermediate end products. Thereby, the biphasic medium facilitates the separation of these products which were soluble only in the organic phase of this system. These intermediate end products showed higher anti-leishmania activity against L. tropica promastigotes than (+)-catechin and glucantime. Additionally, enzymatic oxidation led to amplifying the radical scavenging activity against the superoxide anion and cytotoxic activity toward HUVEC cells compared with a (+)-catechin monomer. Furthermore, oxidation end products inhibited xanthine oxidase activity. Consequently, this enzymatic procedure in hydro-organic medium could provide new compounds presenting optical, antileishmanial, antioxidant and cytotoxic interest. تم في هذه الدراسة التحري وبطريقة صديقة للبيئة عن أمكانية تركيب مركبات مشابهة للطبيعية ومستقرة عن طريق الاكسدة الانزيمية للكاتيشين المحفزة بإنزيم اللاكاز في وسط ثنائي الطور ( عضوي _مائي). اختير الكاتيشين كونه يشكل احدى الفلافونيدات الاكثر فعالية والموجودة في غذاء الانسان، بالإضافة الى امتلاكه للعديد من الخصائص الحيوية المهمة. كذلك، هدف هذا البحث الى استغلال الاكسدة الانزيمية للكاتيشين المحفزة بإنزيم اللاكاز في وسط ثنائي الطور ( عضوي _مائي) بهدف زيادة انحلالية النواتج ومنع اسمرارها اللاحق وتحسين خصائصها الحيوية. تمت أكسدة الكاتيشين المحفزة بإنزيم اللاكاز من فطر Myceliophthora thermophila في وسط مائي ووسط ثنائي الطور ( عضوي _ مائي) بهدف إنتاج جزيئات حيوية جديدة. سمحت تقنية الترشيح الفائق لإنزيم اللاكاز التجاري بإزالة الملوثات الفينولية وزيادة الفعالية النوعية للإنزيم بمقدار ضعفين. أفضت أكسدة الكاتيشين في نظام ثنائي الطور(عضوي – مائي) الممزوج بشكل تام والمكون من دارئة فوسفاتية والاتيل اسيتات إلى نواتج برتقالية اللون وذات ثباتية عالية. بالمقارنة مع الوسط المائي، يقدم الوسط ثنائي الطور (عضوي – مائي) العديد من الايجابيات المهمة مثل التقليل من الفعالية الإنزيمية والزيادة في الوقاية من تطور تفاعلات السمرة الأنزيمية اللاحقة، وكذلك زيادة انحلالية وثباتية النواتج الوسيطة النهائية للتفاعل. وبناء عليه، يمكن القول بأن الوسط ثنائي الطور يسهل فصل هذه النواتج والتي تكون عادة منحلة فقط في الطور العضوي لهذا النظام. في الواقع، أبدت هذه النواتج الوسيطة النهائية في الزجاج فعالية مضادة لليشمانيا وخصوصا مشيقات الليشمانيا المدارية L. tropica اكبر من الكاتيشين والدواء المرجعي (الغلوكانتيم). علاوة على ذلك، مكنت الأكسدة الأنزيمية من زيادة الفعالية الممخلبة لشوارد الأكسجين المؤكسدة الحرة والسمية الخلوية تجاه الخلايا المشتقة من البطانة الداخلية للحبل السري HUVEC)) بالمقارنة مع جزيء الكاتيشين الأحادي غير المؤكسد. أيضا، أظهرت النواتج النهائية لأكسدة الكاتيشين قدرة تثبيطية لفعالية أنزيم الأكزنتين اوكسيداز والمسبب لتراكم حمض البول في الجسم. وبالنتيجة، مكنت هذه الطريقة الأنزيمية في وسط ثنائي الطور(عضوي – مائي) من الحصول على مركبات جديدة والتي تجسد العديد من الخصائص المهمة مثل اللون والفعالية المضادة لليشمانيا والمضادة للأكسدة والسمية الخلوية والفعالية المضادة لأنزيم الاكزنتين اوكسيداز، مما يجعلها مرشحة للاستخدام في العديد من الصناعات الصيدلانية والغذائية والطبية.